Process Optimization of Finger Millet Incorporated Extrudates - KC, Yadav; Rajbanshi, Ranjit; Bhattarai, Prabesh; Dhungana, Pramesh K.; Subba, Dilip (Himalayan Journal of Science and Technology, 2020)
The effects of incorporation of finger millet (Eleusine coracana L.) flour and extrusion conditions on physico-chemical characteristics of corn grit- rice grit-chickpea flour blend expanded extrudates were studied. Response surface methodology was used to study the effects of level of incorporation of millet flour in feed composition (5 to 25 %), feed moisture (12-16%), screw speed (1000-1400 rpm) and extrusion temperature (80–120°C). Single screw extruder was used for the experiments. The level of millet flour incorporation had significant effect on water solubility index (p